2020
DOI: 10.1101/2020.07.29.226464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sero-prevalence and risk factors of leptospirosis in commercial cattle herds of Rupandehi district, Nepal

Abstract: Nepal has an agrarian-based economy where the livestock sector contributes about 12 percent to the national GDP. Rupandehi district is one of the largest dairy pocket areas in the nation, but the disease, such as leptospirosis, posed a negative impact on their production and productivity. Despite the economic importance of cattle leptospirosis, the disease is concerned for the people’s occupational risk and food safety. Although leptospirosis is a priority zoonosis in Nepal, the effective implementation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the Netherlands, studies carried out during 2017-2021 indicate that L. Hardjo infections were detected in 120 dairy herds [29]. The authors' studies [30] in Egypt showed that 39.33% of the 236 studied animals had antibodies to leptospirosis. A total of 48 randomly selected cattle herds were studied in Algeria between 2015 and 2019.…”
Section: Resultsmentioning
confidence: 96%
“…In the Netherlands, studies carried out during 2017-2021 indicate that L. Hardjo infections were detected in 120 dairy herds [29]. The authors' studies [30] in Egypt showed that 39.33% of the 236 studied animals had antibodies to leptospirosis. A total of 48 randomly selected cattle herds were studied in Algeria between 2015 and 2019.…”
Section: Resultsmentioning
confidence: 96%
“…Rodents were a risk factor for four serogroups in the study. In Nepal, the relationship between rodents and the disease is reported (Gompo et al, 2020); in Brazil (Fávero et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, Leptospira spp. is associated with the presence of canines (Gompo et al, 2020), an essential reservoir of the disease, especially when there are no entry controls for this species. The study suggests that the serogroup Canicola and Grippotyphosa correlated more with environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study from 2019 to 2020, 206 cattle herds were visited and 383 serum samples were collected in the Rupandehi district of Nepal. These were tested against L. Hardjo with an ELISA (Prionics Lelystad B.V., The Netherlands), and 3.81% tested positive [ 32 ]. As in this study, the L. Hardjo antibody prevalence was also low in our study in Bhutan.…”
Section: Discussionmentioning
confidence: 99%